LOGICO-SEMANTIC RELATION OF CLAUSES USED IN ANALYTICAL EXPOSITION WRITTEN BY THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT - Rizka Yuniar (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
In Indonesia, English language teaching concerns with text or genre. Consequently, systemic functional linguistics is important to apply in writing a text. However, students have difficulties of grammar, vocabulary, and how to construct word into syntactical construction. Students only concern with how to compose a text however it contains meaningless clauses. The writer is interested to choose a problem of constructing clause complex as source of the research.The objectives of this research are to identify the kinds of logico-semantic relation and to analyze the logico-semantic relation of clauses mostly used in analytical exposition written by the third semester students of Tidar University in the academic year 2017/2018.This study applies descriptive qualitative research which consists of detail description and explanation of logico-semantic relation of clauses in students’ writing. In conducting this research, the writer collected the documentation of students’ writing about analytical exposition. The data were analyzed by classifying the clauses and identifying kinds of logico-semantic relation proposed by Halliday and Matthiessen (2014).Based on data analysis, it can be concluded that the analytical exposition texts analyzed in this research contain more logico-semantic relation of clauses such as expansion (elaboration, extension and enhancement) and projection (locution). It is noticed that expansion of enhancement is mostly used in the texts with 31 times or 41.89% of total occurrance and although the texts still need improvement in making a clause complex.